Transcription Factor GmWRKY46 Enhanced Phosphate Starvation Tolerance and Root Development in Transgenic Plants - Li, Cheng; Li, Kangning; Liu, Xinyi; Ruan, Hui; Zheng, Mingming; Yu, Zhijie; Gai, Junyi; Yang, Shouping (Frontiers in Plant Science, 2021)
Phosphorus (P) is one of the essential macronutrients, whose deficiency limits the growth and development of plants. In this study, we investigated the possible role of GmWRKY46 in the phosphate (Pi) starvation stress tolerance of soybean. GmWRKY46 belonged to the group III subfamily of the WRKY transcription factor family, which was localized in the nucleus and had transcriptional activator activity. GmWRKY46 could be strongly induced by Pi starvation, especially in soybean roots. Overexpression of GmWRKY46 significantly enhanced tolerance to Pi starvation and lateral root development in transgenic Arabidopsis. RNA-seq analysis showed that overexpression of GmWRKY46 led to change in many genes related to energy metabolisms, stress responses, and plant hormone signal transduction in transgenic Arabidopsis. Among these differential expression genes, we found that overexpression of AtAED1 alone could enhance the tolerance of transgenic Arabidopsis to Pi starvation. Y1H and ChIP-qPCR analyses showed that GmWRKY46 could directly bind to the W-box motif of the AtAED1 promoter in vitro and in vivo. Furthermore, results from intact soybean composite plants with GmWRKY46 overexpression showed that GmWRKY46 was involved in hairy roots development and subsequently affected plant growth and Pi uptake. These results provide a basis for the molecular genetic breeding of soybean tolerant to Pi starvation.